I am Singapore. - Leong, Stefanie Seok Hoon. (2010)
Singaporeans often do not associate the larger national identity with their personal identity. This emotional detachment with the self is quite a trend among Singaporeans. It is interesting to find out that Singaporeans automatically have a negative view towards the Singaporean. However, this Singaporean identity is not a separate entity. The words and descriptions we choose are a true reflection of the self. “i AM Singapore.” presents my satirical society, Singapore, in a humourous yet reflective approach. Are we being too hard on ourselves or do we take pride and joy in making fun at ourselves?